A DRAINAGE SEDIMENT GEOCHEMICAL ORIENTATION STUDY KEBAN, ELAZIG, EASTERN TURKEY - Bolucek, Cemal; Kalender, Leyla (Springer Heidelberg, 2009)
An orientation stream sediment survey was conducted in a semi-arid area of western Elazig province, eastern Turkey, in order to optimize grain size selection and analytical procedures for delineating mineralization and differentiating bedrock types. Samples were collected from ephemeral streams and water-bearing rivers in which the -180 mu m fraction had previously been found to be effective in delineating most of the known mineralization. Thirteen stream sediment samples were sieved into five size fractions (-850+600 mu m, -600+180 mu m, -180+106 mu m, -106+75 mu m, -75 mu m). These and the previously analyzed -180 mu m fractions were digested using aqua regia, -180+106 mu m fractions were digested using weak cyanide leach. All samples were analyzed for a variety of elements by ICP-MS after both digestions. Higher concentrations of nearly all elements are typically found in the finest grain size fraction (silt and clay, <75 mu m), which usually represents less than 3 wt% of the stream sediment samples. Geochemical anomalies, mainly in the ephemeral streams, extend several hundreds of meters downstream from the known Pb, Zn, and Cu-bearing veins, which could be delineated by element dispersion patterns obtained by both extractions. Previously unknown Au anomalies were detected in the southwestern part of the study area, which was shown only by the aqua-regia extractable gold anomalies. These results suggest that weak cyanide leaching may offer an acceptable alternative to aqua regia analysis for Cu, Zn, Mo, Co, Ag, and Hg in this environment.
Keywords: partial digestion; stream sediment; semi-arid; Turkey